Did I find the right examples for you? yes no

All Samples(14)  |  Call(12)  |  Derive(0)  |  Import(2)

src/s/y/sympy-HEAD/sympy/integrals/tests/test_transforms.py   sympy(Download)
from sympy.integrals.transforms import (mellin_transform,
    inverse_mellin_transform, laplace_transform, inverse_laplace_transform,
    fourier_transform, inverse_fourier_transform,
    sine_transform, inverse_sine_transform,
    cosine_transform, inverse_cosine_transform,
    assert cosine_transform(f(t), t, w) == CosineTransform(f(t), t, w)
    assert inverse_cosine_transform(
        f(w), w, t) == InverseCosineTransform(f(w), w, t)
 
    assert cosine_transform(1/sqrt(t), t, w) == 1/sqrt(w)
    assert inverse_cosine_transform(1/sqrt(w), w, t) == 1/sqrt(t)
    assert cosine_transform(t**(
        -a), t, w) == 2**(-a + S(1)/2)*w**(a - 1)*gamma((-a + 1)/2)/gamma(a/2)
    assert inverse_cosine_transform(2**(-a + S(
        1)/2)*w**(a - 1)*gamma(-a/2 + S(1)/2)/gamma(a/2), w, t) == t**(-a)
 
    assert cosine_transform(
        exp(-a*t), t, w) == sqrt(2)*a/(sqrt(pi)*(a**2 + w**2))
    assert inverse_cosine_transform(
        sqrt(2)*a/(sqrt(pi)*(a**2 + w**2)), w, t) == exp(-a*t)

src/s/y/sympy-0.7.5/sympy/integrals/tests/test_transforms.py   sympy(Download)
from sympy.integrals.transforms import (mellin_transform,
    inverse_mellin_transform, laplace_transform, inverse_laplace_transform,
    fourier_transform, inverse_fourier_transform,
    sine_transform, inverse_sine_transform,
    cosine_transform, inverse_cosine_transform,
    assert cosine_transform(f(t), t, w) == CosineTransform(f(t), t, w)
    assert inverse_cosine_transform(
        f(w), w, t) == InverseCosineTransform(f(w), w, t)
 
    assert cosine_transform(1/sqrt(t), t, w) == 1/sqrt(w)
    assert inverse_cosine_transform(1/sqrt(w), w, t) == 1/sqrt(t)
    assert cosine_transform(t**(
        -a), t, w) == 2**(-a + S(1)/2)*w**(a - 1)*gamma((-a + 1)/2)/gamma(a/2)
    assert inverse_cosine_transform(2**(-a + S(
        1)/2)*w**(a - 1)*gamma(-a/2 + S(1)/2)/gamma(a/2), w, t) == t**(-a)
 
    assert cosine_transform(
        exp(-a*t), t, w) == sqrt(2)*a/(sqrt(pi)*(a**2 + w**2))
    assert inverse_cosine_transform(
        sqrt(2)*a/(sqrt(pi)*(a**2 + w**2)), w, t) == exp(-a*t)